Coaching clinic strategi penulisan naskah bagi mahasiswa pascasarjana Indonesia di Taiwan - Siswanto, Ibnu; Rahmawaty, Penny; Hidayati, Lina Nur; Arifin, Achmad (Universitas Sarjanawiyata Tamansiswa, 2025)
Taiwan merupakan salah satu negara yang memiliki sistem Pendidikan tinggi terbaik dan menjadi alasan bagi sekitar 5.600 mahasiswa Indonesia untuk menempuh S2 dan S3 di negara tersebut. Salah satu persyaratan kelulusan program pascasarjana di universitas khususnya Taiwan adalah publikasi pada jurnal internasional bereputasi (Terindex SCI/SSCI) yang sering menjadi kendala bagi mahasiswa pascasarjana untuk menyelesaikan studinya tepat waktu. Oleh karena itu, kegiatan pengabdian kepada Masyarakat ini bertujuan untuk melakukan manuscript coaching clinic bagi mahasiswa pascasarjana di Taiwan sehingga manuskrip dapat terbit di jurnal internasional bereputasi. Kegiatan dilaksanakan pada tanggal 25-26 Agustus 2023 di Sekretariat Forum Mahasiswa Muslim Indonesia di Taiwan (FORMMIT) National Central University, Taiwan. Hasil kegiatan yaitu dapat peserta menghasilkan draft manuscript dan manuscript yang akan disubmit di jurnal Internasional, dokumen kerjasama antara Fakultas Teknik serta Fakultas Ekonomi dan Bisnis dengan FORMMIT, terlaksananya sosialisasi studi lanjut S2 dan S3 ke Taiwan bagi mahasiswa UNY. Coaching clinic for manuscript writing strategy for Indonesian post-graduate students in Taiwan Abstract: Taiwan is one of the countries that has the best higher education system and is the reason for around 5,600 Indonesian students to take Masters and Doctoral degrees in Taiwan. One of the requirements for graduating from postgraduate programs at universities in Taiwan is publication in reputable international journals (SCI/SSCI Indexed), which often becomes an obstacle for postgraduate students to complete their studies on time. Therefore, this community service activity aims to conduct a manuscript coaching clinic for postgraduate students in Taiwan so that the manuscript can be published in a reputable international journal. The activity was held on 25-26 August 2023 at the Secretariat of the Indonesian Muslim Student Forum in Taiwan (FORMMIT) at National Central University, Taiwan. Output of the community services are participants’ manuscripts which will be submitted in international journals, cooperation documents between the Faculty of Engineering and the Faculty of Economics and Business with FORMMIT, and implementation of socialization for further Masters and Doctoral studies to Taiwan for UNY students.